THE EFFECT OF "QUANTUM LEARNING" MODEL USING "MIND MAPPING" TECHNIQUE TO EIGHT GRADE STUDENTS’ CREATIVE THINKING ABILITY - Eriyanto, Erik; Inganah, Siti; Utomo, Dwi Priyo (MEJ (Mathematics Education Journal), 2019)
This study aims to determine how the effect of the Quantum Learning model using Mind Mapping techniques to students' creative thinking abilities. The type of research used is experiment and quantitative approach with research design using posttest only group design. Data analysis of two groups used the t-test on SPSS 21, that is Independent Sample t-Test to test the difference in average posttest value of two samples.The results of this study are (1) results of the t-test  from post-test data obtain a significance 0,000 where it is lower than 0.05 so can be said that the average of the two groups are different, (2) from the post-test results, the answers given by students from the experimental group more fulfilled the indicators of creative thinking than students from the control group.